Agrotóxicos no Brasil: Padr\~oes de uso, política da regulaç\~ao e prevenç\~ao da captura regulatória - Rodrigo Fracalossi de Moraes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– Pesticides are not only agricultural inputs but also dangerous products, reason why the state must regulate them. However, if scientific evidence about the effects of pesticides is universal, why do regulations vary across countries? This article argues that pesticide regulation depends in part on the relative power of groups that gain and that lose with a certain type of regulation. Regulations are not created and implemented by politicallyneutral state agencies: they result from the relative influence of organized groups. In this "game", groups that concentrate costs or benefits of a hypothetical regulation have more incentives to mobilize than groups for which costs or benefits are diffuse. Yet, this does not prevent the latter from influencing the regulatory process, mainly through norms and scientific knowledge. The text also analyses how the use of pesticides evolved in Brazil since the beginning of the 1990s, focusing on how their use is concentrated in some crops and regions. Finally, the paper suggests a set of policies, with emphasis on preventing regulatory capture: i) maintaining a system of registration of pesticides not centralized in agencies working only to promote agricultural production; ii) creating mechanisms to prevent what the literature calls the "revolving door" problem; iii) increasing the participation of civil society organizations and experts; iv) training civil servants on relations with the private sector, regulation and regulatory capture; and v) maintaining guarantees for the freedom of expression and opinion. Finally, the text explores the potential effects of north-south dynamics on the pesticide regulation in Brazil, especially the fact that the production of pesticides in Brazil is controlled by multinational companies.
Keywords: Q15; Q18; 330; pesticides; politics of regulation; special interest groups; advocacy networks; regulatory capture